Ichthyocenosis of the upper epipelagic layer in the Pacific waters of Russia during japanese sar-dine «renaissance» in the beginning of the 21st century - O. A. Ivanov; V. I. Radchenko; V. P. Shuntov; A. N. Starovoitov (Известия ТИНРО)
Dynamics of integral parameters for the species structure in ichthyocenosis of the upper epipelagic layer in the Pacific waters off the Kuril Islands in 2019–2023 is discussed in compare with previously published data since 2004 in context of a new bloom of japanese sardine Sardinops melanostictus. Results of trawl surveys are clustered using the method of multi-dimensional scaling. Species composition in the trawl catches in 2004–2013, before the time of mass expansion of subtropi-cal migrants, as japanese sardine and chub mackerel Scomber japonicus, was distinguished by domina-tion of mesopelagic fishes of families Myctophidae and Microstomatidae and pink salmon Oncorhynchus gorbuscha. From 2014 to the present, the dominant positions in the ichthyocenosis were held by japanese sardine and chub mackerel, with a decreasing role of the latter. In the last pentade (2019–2023), the species structure of pelagic ichthyocenosis in the Pacific waters of Russia has not undergone fundamental changes. At the same time, the tendency has increased for uneven distribution of biomass between the species of fish community in favor of japanese sardine. The polydominance index decreased significantly (P < 0.05, t-test 4.33) from 4.85 ± 0.44 in 2004–2013 to 2.37 ± 0.21 in 2019–2022, and the index of evenness of species structure decreased from 0.41 ± 0.04 to 0.15 ± 0.02 (P < 0.05, t-criterion 5.25). Growth of domestic and foreign catches of japanese sardine in the second decade of the 21 century is a sign of this species bloom beginning.